Analisis Kepuasan Masyarakat Terhadap Pelayanan Publik - Azwar, Hanifah (Universitas Indraprasta PGRI, 2019)
This study aims to analyze public satisfaction with public services (BPJS Health case studies in the Cikarang Industrial Area) in term of internal and external aspects so BPJS Health Care's performance and service can be seen to provide the satisfaction for customers. The external aspects analysis including the dimensions of rate new customer acquisition, customer acquisition, responding customer complaint, customer satisfaction and customer benefit. The analysis of the internal aspects including the dimensions of innovation, operation and after sales service. The Methode of this research is mixed method. Data collection techniques used in this research is quantitative and qualitative type with the descriptive design. The result of the study is, still there are the indicators of satisfaction which still delivery below expectations, indicated by the gap between customer expectations with services perceived. There are still a shortcomings perceived, espesially in the service delivery in the process of services performance of National Social and Healthcare Security (BPJS) that has been run. The advice is the improvement of the service performance attributes that are still perceived below expectations, as well as the increased service performance in providing inpatient, medical personnel and human resources.